2007
DOI: 10.1136/pgmj.2006.050112
|View full text |Cite
|
Sign up to set email alerts
|

Importance of red patches diagnosed in cystoscopy for haematuria and lower urinary tract symptoms

Abstract: Background: Biopsy of the red patches in the bladder, when found at cystoscopy, is routinely performed in urological practice. This is done to establish the sinister diagnosis of carcinoma-in-situ among other causes. Objective: To analyse the pathology of the red patches and to determine if routine biopsy of these patches is warranted. Patients and methods: This was a retrospective study conducted over a period of 36 months, in which 50 patients were identified, who underwent biopsies of their red patches. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
3
2
0
Order By: Relevance
“…In patients less than 60 years old in this study, biopsies of red patches were negative for neoplasia [125]. Fernando et al found a similar age range (60-70 years) for positive biopsies and found that red patch biopsies were positive for CIS in four out of 25 patients [126]. Prudent cystoscopic examination, therefore, should include sampling of areas with erythema, elevation or erosion, as well as diverse random sampling of grossly normal bladder mucosa in a high-risk patient.…”
Section: Fluorescence Cystoscopysupporting
confidence: 70%
“…In patients less than 60 years old in this study, biopsies of red patches were negative for neoplasia [125]. Fernando et al found a similar age range (60-70 years) for positive biopsies and found that red patch biopsies were positive for CIS in four out of 25 patients [126]. Prudent cystoscopic examination, therefore, should include sampling of areas with erythema, elevation or erosion, as well as diverse random sampling of grossly normal bladder mucosa in a high-risk patient.…”
Section: Fluorescence Cystoscopysupporting
confidence: 70%
“…There is also a significant association between age >70 and the presence of flat lesions(dysplasia/CIS) in association with carcinoma This goes with previous studies by Cheng et al (21) , Demir et al (22) , Fernando et al (23) , Garbar et al (24) and Takenaka et al (9) . In the present study, the majority of the studied cases of flat lesions including CIS were males (88.3%).…”
Section: Significance Of Flat Epithelial Lesions Of the ………supporting
confidence: 85%
“…In our present a statistically significant relationship was observed between age <50 and the presence of isolated flat lesions. There is also a significant association between age >70 and the presence of flat lesions(dysplasia/CIS) in association with carcinoma This goes with previous studies by Cheng et al (21) , Demir et al (22) , Fernando et al (23) , Garbar et al (24) and Takenaka et al (9) . In the present study, the majority of the studied cases of flat lesions including CIS were males (88.3%).…”
Section: Significance Of Flat Epithelial Lesions Of the ………supporting
confidence: 85%